The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.17113/ftb.55.03.17.4873
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High Pressure and Subzero Temperature on Gelation of Washed Cod and Salmon Meat

Abstract: The objective of the present work is to examine the influence of pressure up to 193 MPa at subzero temperature (without freezing of water) on myofibrillar proteins of salmon and cod meat and on the properties of gels obtained from washed mince of these fish. The solubility of proteins from myofibrils of cod and salmon meat suspended in 100 mM KCl solution increased after treating the samples with pressure above 60 MPa. The results of SDS- -PAGE analysis showed that under these conditions two myosin light chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…At 20°C bacteria were more susceptible to chitosan than at 4°C (Tables 2 and 3). These results confirmed our earlier data obtained with a limited number of bacteria species [38]. Also Tsai and Su [39] showed that within the range of 4 to 37°C, chitosan antibacterial activity increased with the increasing temperature.…”
Section: Symbol Of Samplesupporting
confidence: 91%
“…At 20°C bacteria were more susceptible to chitosan than at 4°C (Tables 2 and 3). These results confirmed our earlier data obtained with a limited number of bacteria species [38]. Also Tsai and Su [39] showed that within the range of 4 to 37°C, chitosan antibacterial activity increased with the increasing temperature.…”
Section: Symbol Of Samplesupporting
confidence: 91%
“…Milk enzymes, such as catalase, participate in milk H 2 O 2 degradation. Interestingly, Malinowska-Pańczyk et al [ 24 ] highlighted that the milk antioxidant enzyme superoxide dismutase (SOD) activity is increased by HHP. Therefore, it could be plausible that other enzymes implicated in ROS degradation, such as catalase, may also be sensitive to HHP, thus promoting H 2 O 2 degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike most food proteins, myofibrillar protein self‐assembles filamentous structure largely via electrostatic attractions between charged clusters in the myosin‐rod amino acid residues. Previous studies demonstrated that electrostatic attraction in proteins could be disrupted under mechanic forces, like high pressure (Malinowska‐Pańczyk & Kołodziejska, 2017) and cavitation (Liu et al., 2020). Some of these released charged groups might be exposed onto the surface of protein molecules, which block the reassembly of protein molecules.…”
Section: Introductionmentioning
confidence: 99%